Entailments, pragmatic assertion and mood in Spanish complements - Mejías-Bikandi, Errapel (Borealis – An International Journal of Hispanic Linguistics, 2016)
This paper examines a frequently overlooked class of expressions in Spanish that license the subjunctive mood in a complement clause. This class contains expressions such as poco/a/s “few”, menos de “less than” and solo “only”. The goal of the paper is to offer an account of the use of mood with these expressions that incorporates the data under discussion into previous pragmatic accounts of mood based on notions of assertion and informative value. The paper first offers a semantic characterization of this class of expressions that is based on their monotonic properties (Ladusaw 1980, Ladusaw 1983). Next, it explores the pragmatic effects of their semantic properties. Following Stalnaker (1978), I assume that the effect of a pragmatic assertion is to reduce the set of possible worlds that represents the presuppositions held by a speaker and their audience (referred to as the context set). It is argued that propositions under the scope of an upward entailing expression are more informative, and they are thus more relevant and higher in a scale of assertability (Lunn 1989), in that they allow for inferences that further reduce the context set. Propositions under the scope of expressions that are not upward entailing lose some of their informative value, and thus they are lower in the scale of assertability, which correlates with the possibility of using subjunctive mood in a complement under their scope.
Keywords: Spanish Complements; Verbal Mood; Subjunctive; Semantics; Pragmatic Assertion.